Plasmodium Falciparum: A Pathogenesis and Therapeutic Challenges in Combating Fatal Malaria: A Subject Review - Shakour, Sunbul Jalal (American Journal of Biomedicine and Pharmacy, 2026)
Plasmodium falciparum is the most lethal malaria parasite worldwide with characteristic mature gametocytes of the crescentic form and intricate capacity by sequestration in the microvasculature of host. Its life cycle is a complex change between the Anopheles mosquito and human host with a silent hepatic phase followed by an erythrocytic pathogenic one that occurs every 48 hours. Avoidance of the host’s immune response is effected by the rapid shift of expression from one PfEMP1 variant to another through antigenic variation on the surface of infected erythrocytes, mediated by 'patching' and 'segmental gene conversion'. Although Iraq has achieved an elimination status with no autochthonous transmission, the risk of re-importation and resurgence are high because of imported cases from neighboring endemic countries (Iran) and it is also under threat of vector expansion as a result of climatic changes. New management has shifted to rapid diagnostic tests and the Artemisinin-based Combination Therapies (ACTs) As well as the elimination by 2030, it faces biological and ecological issues.